Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Minat Belajar Siswa Pada Mata Pelajaran Matematika di SDN Sumbersari 3 Malang: Penelitian - Akbar Maulana Malik Ibrahim; Sa’dun Akbar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach on the interest in learning mathematics of third grade students of SDN Sumbersari 3 Malang. The background of this study is the low interest of students in learning mathematics subjects which are considered difficult and boring. This study used a quantitative approach with a pre-experiment design type one group pretest-posttest design. The research subjects were 20 third grade students. Data collection was carried out through a learning interest questionnaire given before and after the application of the RME approach. The data obtained were analyzed descriptively and inferentially. The results showed a significant increase in students' interest in learning mathematics after the application of the RME approach. Students became more active, enthusiastic, and involved in the learning process. This shows that the contextual and student-centered RME approach is able to increase their learning motivation. It can be concluded that the RME approach has a positive effect on students' interest in learning mathematics and can be used as an alternative interesting learning strategy at the elementary school level.